2014
DOI: 10.1111/jvs.12213
|View full text |Cite
|
Sign up to set email alerts
|

From facilitative to competitive interaction between Larrea tridentata and Cylindropuntia leptocaulis in the southern Chihuahuan Desert

Abstract: Question Can the co‐existence of the cactus and the shrub in the community be driven by a cyclic succession mechanism? Location Mapimí Biosphere Reserve (southern Chihuahuan Desert). The vegetation is scrub, dominated by Larrea tridentata. Methods Interspecific spatial association between adult L. tridentata and differently sized Cylindropuntia leptocaulis plants was analysed using Ripley′s K function, exploring the hypothesis that facilitation causes differential recruitment of cactus below the shrub and a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 65 publications
(141 reference statements)
2
15
0
Order By: Relevance
“…Based on Yeaton () and our own observations (Flores‐Torres & Montaña, ), we expected the change of status from associated to solitary to be a relatively rare event. Indeed, over the 7‐year period, only 17 out of the initial 314 LA died resulting in 17 CA becoming CS (5.4% or <0.8% per year).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Yeaton () and our own observations (Flores‐Torres & Montaña, ), we expected the change of status from associated to solitary to be a relatively rare event. Indeed, over the 7‐year period, only 17 out of the initial 314 LA died resulting in 17 CA becoming CS (5.4% or <0.8% per year).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to this hypothesis, Flores‐Torres and Montaña () found that recruitment of C. leptocaulis under L. tridentata shrubs in the Southern Chihuahuan Desert was mostly via vegetative propagation of stem segments rather than from seed. They also found that, although Larrea facilitates the clonal establishment of the cactus, it is rarely replaced by it (Flores‐Torres & Montaña, ). Long‐term coexistence of the individual plants would suggest that the hypothesised cyclical dynamics of replacement might in fact not occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of hydraulic descent increases as the root depth of woody plants increases; in these conditions trees exert a competitive rather than a facilitative effect on CAM plants in access to soil water. In fact, it has been proposed that CAM plants that are facilitated during their establishment stage competes with and even excludes their nurse plants (woody plants) as an adult (e.g., Withgott, 2000) due to ontogenetic changes in the interacting species, but the experimental evidences are scare (e.g., Flores-Martinez et al, 1994;Flores-Torres and Montana, 2015). The role of hydraulic descent in turning facilitation of CAM plants by woody plant to competition as shown in this study may explain why CAM plants (which benefit from the presence of trees during their establishment), once they become adults they are not strong enough to outcompete their nurse plants (i.e., trees), consistent with field observations (i.e., Reyes-Olivas et al, 2002;Flores-Torres and Montana, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been proposed that CAM plants that are facilitated during their establishment stage competes with and even excludes their nurse plants (woody plants) as an adult (e.g., Withgott, 2000) due to ontogenetic changes in the interacting species, but the experimental evidences are scare (e.g., Flores-Martinez et al, 1994;Flores-Torres and Montana, 2015). The role of hydraulic descent in turning facilitation of CAM plants by woody plant to competition as shown in this study may explain why CAM plants (which benefit from the presence of trees during their establishment), once they become adults they are not strong enough to outcompete their nurse plants (i.e., trees), consistent with field observations (i.e., Reyes-Olivas et al, 2002;Flores-Torres and Montana, 2015). In view of the universal ability of woody plants to perform hydraulic redistribution (e.g., Neumann and Cardon, 2012;Prieto et al, 2012), the role of hydraulic descent benefiting trees may contribute to my understanding tree-CAM association/coexistence widely documented in different arid and semiarid zones including the Sonoran and Chihuahuan deserts (e.g., Hutto et al, 1986;Drezner, 2007;Flores-Torres and Montana, 2015), the Zapotitlán de las Salinas or Tehuacan valley, central…”
Section: Discussionmentioning
confidence: 99%